Corruption risk as a structural driver of state fragility: examining the governance crisis in South Africa - Mkhize, Nkosingiphile; Nel-Sanders, Danielle (Frontiers in Political Science, 2025)
IntroductionCorruption remains a critical governance challenge globally, yet its role in perpetuating state fragility is underexplored in political science literature. In the South African context, corruption extends beyond ethical or administrative failings, functioning as a structural disorder that erodes institutional resilience, economic development, and political stability.MethodsThis study employs a thematic content analysis, integrating empirical evidence and governance risk frameworks to examine the systemic nature of corruption and its impact on state fragility.ResultsThe analysis identifies four key dimensions through which corruption exacerbates governance fragility: institutional weakening and bureaucratic dysfunction; economic stagnation and developmental failure; erosion of public trust and legitimacy; and the perpetuation of a corruption–fragility cycle. The findings reveal that corruption sustains a self-reinforcing dynamic that obstructs reform and deepens state vulnerability.DiscussionThe results underscore the necessity for comprehensive anti-corruption strategies that move beyond punitive measures. Strengthening institutional integrity, promoting economic diversification, and enhancing public accountability are crucial to breaking the corruption–fragility cycle. By framing corruption as a central determinant of political and economic instability in fragile states, this study contributes to advancing scholarship on governance, state resilience, and sustainable development.